A STUDY OF COMPETENCE MODEL FOR FIVE-YEAR JUNIOR COLLEGE STUDENTS TAKING INTERNSHIP IN HAIRDRESSING INDUSTRY (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2022)
The paper aims to analyze the competence model for vocational college students taking internship in hairdressing industry based on the viewpoints of learning by doing, based on the discourses from Dewey’s experience theory and to understand the correlation and hierarchy of the context of competence for the professional skills of hairdressing industry, thereby to facilitate the design and development of human resources for the hairdressing industry. The study analyzes the off-campus interns for junior college cosmetology andhairdressing related departments in Taiwan. The study also emphasizes on school teachers, hairdressing personnel and hairdressing industry interns through conducting qualitative research document analysis, and quantitative research ISM system. The analysis of context and correlation of competence skills for hairdressing industry can be adopted as the standard of occupational information for designing hairdressing competence and learning map by schools and vocational institutes. Secondly, the study will link hairdressing personnel development with hairdressing industry demand to create win-win situations for school course instrument, industry education training and employment of industry personnel.